MODERN MILK FORMULAE IN INFANT FEEDING - Ye.N. Kozhevnikova ("Paediatrician" Publishers LLC, 2006)
The article highlights the data of changes in the production line of the modern infant foodstuffs manufactured by Semper company. Along with that, it briefly describes the properties of each product and latest clinical investigations in the field of infant food. Key words: children, infant food, human milk substitute, protein, iron